Effect of Piezoelectric Phase on Electrical Properties of PDMS-Based Nanocomposites - Patiparn Kongjaiman; Preedaporn Yunsamarn; Wanwilai Vittayakorn (Integrated ferroelectrics, 2021)
In this work, nanocomposite between polydimethylsiloxane (PDMS) and barium titanate (BT) are prepared in order to use as piezoelectric nanogenerator. Barium titanate phase with various amounts and shapes such as nanoparticles and nanowires are synthesized via appropriated methods. The PDMS and BT phases are homogeneously mixed and casted into 3 cm x 4 cm rectangle. Phase formation, chemical property and microstructure of these nanocomposites are identified via XRD, FTIR and SEM methods, respectively. Both frequency and temperature dependences of dielectric properties for all samples are measured by LCR meter. The piezoelectric properties of these nanocomposites are performed by study the generated output voltage and current after applying the mechanical force to the samples. From those results, it is concluded that the electrical properties of these BT/PDMS nanocomposites strongly depend on amounts and forms of piezoelectric filler. The orientation of polarization within the BT crystal shows an important role for piezoelectric properties of these nanocomposites.
Keywords: Advanced Sensor and Energy Harvesting Materials; Dielectric materials and actuators; Conducting polymers and applications